PENANAMAN PENDIDIKAN TOLERANSI DALAM PEMBELAJARAN AKIDAH AKHLAK - Nugroho, Emeraldo Wahyu; Effendi, M. Supperapto; Septian, Rahmat Yudhi (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
As an archipelagic country, Indonesia has peace of culture, tribe, clan and religion. Each ethnic group has its own distinctive characteristics and certain characteristics in a special region. Known for its cultural peace, the Indonesian nation has the 1945 Constitution, Pancasila, and the dynamism and dialectic of national life enshrined in Vinneka Tungal Ika. This diversity proves that the Indonesian nation has a heterogeneous character. The custom of openness is very real throughout religions, and although religious education is not one of religious education, the application of the custom of openness in schools is incorporated into the religious education of all religions and beliefs. add. The custom of openness that must be cultivated. The custom of openness can be instilled in many subjects, including religious education. This matter can also be communicated by practicing speaking and mastering comparisons. In the school area, openness is a meaningful view as well as the subject matter of student education. Schools are shown to create a social system consisting of different counter-frameworks, different areas of the house, customs, and moreover different wishful thinking and willpower. Because of this comparison, clashes and problems in daily life do not arise in the school area. The position of the school is to create an airy action for all students. Efforts that can be tried to establish openness by embedding insights into peace, raising devotion to God Almighty through faith programs in schools, and directing all students how to master various forms.